Distributed interactive brain circuits for object-in-place memory: A place for time?. (June 2020) - Aggleton, John P.; Nelson, Andrew J.D.
Rodents will spontaneously learn the location of an individual object, an ability captured by the object-in-place test. This review considers the network of structures supporting this behavioural test, as well as some potential confounds that may affect interpretation. A hierarchical approach is adopted, as we first consider those brain regions necessary for two simpler, 'precursor' tests (object recognition and object location). It is evident that performing the object-in-place test requires an array of areas additional to those required for object recognition or object location. These additional areas include the rodent medial prefrontal cortex and two thalamic nuclei (nucleus reuniens and the medial dorsal nucleus), both densely interconnected with prefrontal areas. Consequently, despite the need for object and location information to be integrated for the object-in-place test, for example, via the hippocampus, other contributions are necessary. These contributions stem from how object-in-place is a test of associative recognition, as none of the individual elements in the test phase are novel. Parallels between the structures required for object-in-place and for recency discriminations, along with a re-examination of the demands of the object-in-place test, signal the integration of temporal information within what is usually regarded as a spatial-object test.